If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(x + -2) = -2x Reorder the terms: X(-2 + x) = -2x (-2 * X + x * X) = -2x (-2X + xX) = -2x Solving -2X + xX = -2x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Reorder the terms: -2X + 2x + xX = -2x + 2x Combine like terms: -2x + 2x = 0 -2X + 2x + xX = 0 The solution to this equation could not be determined.
| 5x+1=2x+17 | | 4(2x*1)=28 | | 3x^2+48x-1260=0 | | 125-3(2X-1)=98 | | 6x+9=4x+1 | | 11b^2-12b-1=b-4+7b^2 | | x-3x-5x=150 | | x-3x-5x=180 | | 12log(9)x+6=0 | | 15-2x=5x+1 | | 2b^2+3b-3=-4 | | 7n+6=10n | | -17(6x)=47+10x | | 20x-(-126)=-9 | | -y+6=15+2y | | 10x+8x-24=x+3 | | 8=7-5x | | m^2-4m=16 | | x+x-9+x+x*0,75=120 | | x+(x-2)+(x+2)=177 | | g(x)=X^2-6x+1 | | -4.9p-2.1p=17.5 | | -4.8n+5.6n=3.6 | | (3x-4)-26=x | | 3x-4-26=x | | 1-0.2k+2.8k=0.48 | | 0.5+0.5a-1.7a=-0.46 | | 3x-4=x-26 | | 1(x+11)=-20(8-x) | | -4v-5.3v=5.58 | | 1+3.7x-0.7x=4.3 | | 3f+19f=4 |